English professional football players concussion knowledge and attitude - Williams, J. M.; Langdon, J. L.; McMillan, J. L.; Buckley, T. A. (Journal of Sport and Health Science, 2016)
Background: Concussions are a common pathology in football and multiple misconceptions exist amongst the players and managers. To address these misconceptions, and potentially reduce concussion associated sequela, effective educational interventions need to be developed. However, the current knowledge and attitude status must be ascertained to appropriately develop these interventions. The purpose of this study was to assess the concussion knowledge and attitude of English professional footballers. Methods: Twenty-six participants from one English Football League Championship club completed the study. A mixed methods approach included the Rosenbaum Concussion Knowledge and Attitudes Survey (RoCKAS) and a semi-structured interview. The RoCKAS contains separate knowledge (0-25) and attitude (15-75) scores and was followed by a semi-structured interview consisting of concussion knowledge, attitude, and behavior related questions. Results: The mean score on the RoCKAS knowledge was 16.4 ± 2.9 (range 11-22) and the attitude score was 59.6 ± 8.5 (range 41-71). The interview responses identified inconsistencies between the RoCKAS and the intended behaviors, endorsing multiple concussion misconceptions, and revealed barriers to concussion reporting. Conclusion: The results of this study suggest that Championship Level English footballers have moderate concussion knowledge, safe attitudes, and good concussion symptom recognition when assessed with pen and paper questionnaires. However, within the semi-structured interview many respondents reported unsafe concussion behaviors despite accurately identifying the potential risks. Further, multiple barriers to concussion reporting were identified which included perceived severity of the injury, game situations, and the substitution rule. These findings can help form the foundation of educational interventions to potentially improve concussion reporting behaviors amongst professional footballers.